2005
DOI: 10.1007/s10344-005-0077-0
|View full text |Cite
|
Sign up to set email alerts
|

A seroprevalence survey of Toxoplasma gondii in common wombats (Vombatus ursinus)

Abstract: Serum was collected from 23 wild common wombats (Vombatus ursinus) on a pastoral property in the Southern Tablelands of New South Wales, Australia (231N 616E) between 3rd August 2001 and 25th March 2002. The serum was tested using three serological methods for antibodies to Toxoplasma gondii. Six animals (26.1%) were shown to have antibodies to T. gondii. The latex agglutination test proved to be less sensitive than the direct agglutination test or the modified agglutination test. This is the first serological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…Their vulnerability to toxoplasmosis is explaining with increased stress factors and immunsupression due to zoo conditions and/or their possibly infrequent contact with feline species during evolution processes (5,6,18). Toxoplasmosis can cause sudden deaths with the absence of prominent clinical findings in captive and wild Australian marsupials, is not always fatal (1,3,4,7,9,18). Clinical findings can be associated with respiratoric, neurologic and gastrointestinal disorders (9,17,18).…”
Section: Bir Kanguruda (Macropus Sp) Sistemik Toksoplasmozismentioning
confidence: 99%
See 3 more Smart Citations
“…Their vulnerability to toxoplasmosis is explaining with increased stress factors and immunsupression due to zoo conditions and/or their possibly infrequent contact with feline species during evolution processes (5,6,18). Toxoplasmosis can cause sudden deaths with the absence of prominent clinical findings in captive and wild Australian marsupials, is not always fatal (1,3,4,7,9,18). Clinical findings can be associated with respiratoric, neurologic and gastrointestinal disorders (9,17,18).…”
Section: Bir Kanguruda (Macropus Sp) Sistemik Toksoplasmozismentioning
confidence: 99%
“…Toxoplasmosis can cause sudden deaths with the absence of prominent clinical findings in captive and wild Australian marsupials, is not always fatal (1,3,4,7,9,18). Clinical findings can be associated with respiratoric, neurologic and gastrointestinal disorders (9,17,18). In the differential and definitive diagnosis of T. gondii infections, serologic (e.g.…”
Section: Bir Kanguruda (Macropus Sp) Sistemik Toksoplasmozismentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have been performed on the clinical manifestations and lesions caused by Toxoplasma gondii in wild animals. Episodes of clinical toxoplasmosis have been reported in macropods (Johnson et al, 1989;Bermú dez et al, 2009), wombats (Vombatus ursinus;Hartley, 2006), black-footed ferrets (Mustela nigripes; Burns et al, 2003), bobcats (Lynx rufus; Dubey et al, 1987;Smith et al, 1995), Pallas cats (Otocolobus manul; Basso et al, 2005), and white-tailed deer (Odocoileus virginianus; Dubey et al, 2008), but until now, no clinical cases have ever been reported in wild pigs (Dubey, 2009). We describe a case of natural congenital transmission of T. gondii in a gestating wild boar (Sus scrofa) that caused fetal malformations and identify the T. gondii types involved.…”
mentioning
confidence: 99%